Efektivitas Pemberian Mobilisasi Dini terhadap Tonus Otot, Kekuatan Otot, dan Kemampuan Motorik Fungsional Pasien Hemiparise Paska Stroke Iskemik: The Effectiveness of Early Mobilization on Muscle Tone, Muscle Strength, and Functional Motor Ability in Patients with Hemiparesis Post Ischemic Stroke - Reni Prima Gusty Gusty (NERS Jurnal Keperawatan, 2012)
Most of the impact of the onset of stroke is weakness in the limbs, leading to decreased productivity and economic ability. Early rehabilitation is needed to reduce these disadvantages, using early mobilization after acute stroke. The research objective was to see the effectiveness of early mobilization on muscular strength, muscle tone, and functional motor skills in hemiparesis after ischemic stroke. This type of research is a quasi-experimental pretest-posttest group design. The subjects were hemiparesis patients after ischemic stroke, distributed into two groups: the first group, consisting of 10 people, was given mobilization training 2 times/day; the second group, consisting of 10 people, was given mobilization training 3 times/day. Training started on day 2 after stroke until day 5. Analysis was conducted using paired and unpaired t-tests, with a significance level of p < 0.05. The results showed an increase in muscle tone, muscle strength, and functional motor ability in both groups, with p = 0.000 for each group. Better improvement was obtained in muscle tone and muscle strength (shoulder, elbow, wrist, thigh, knee, ankle) and functional motor skills in the therapy group that received 3 times/day training compared to the 2 times/day group, with significance values: shoulder muscle strength p = 0.016; elbow muscles p = 0.037; wrist muscles p = 0.042; hamstring muscle p = 0.004; and ankle p = 0.050. Increased ability to tilt to the healthy side p = 0.000; increased ability to sit supine p = 0.000; maintain sitting balance p = 0.007; and the ability to sit up p = 0.007. It is suggested that early mobilization exercise therapy be used as an independent nursing intervention, performed 3 times/day or 2 times/day to help speed recovery and prevent further weakness complications.